Spesolimab: A Novel Interleukin-36 Receptor Monoclonal Antibody for the Treatment of Generalized Pustular Psoriasis - Edla, David Raj; Pasupulati, Haritha; SV Padi, Satyanarayana (Asian Journal of Pharmaceutical Research and Development, 2024)
Psoriasis is an autoimmune condition affecting multiple organs in the body (joints, cardiovascular, and central nervous system), especially the skin. Psoriasis is characterized by inflammation, epidermal hyperproliferation, and aberrant epidermal differentiation. One of the uncommon types of psoriasis is generalized pustular psoriasis (GPP) which is uncommon and associated with increased severity and systemic complications. Early diagnosis is the crucial step in treating GPP to manage its life-threatening complications. Pathogenesis of GPP is still under research. The treatment of GPP aims for symptomatic relief, to remove skin lesions, and to provide supportive care. However, there are no specific guidelines or therapeutic options and it mostly depends on the clinician's opinion that often follows for plaque psoriasis. Accumulating data revealed that the interleukin-36 (IL-36) pathway plays a major role and signaling to favor the pro-inflammatory activity, which is critical in the pathogenesis of GPP, thus starting the maneuver of development of targeted biological therapies for the disease. This article reviews the role of IL-36 in the pathogenesis of GPP and appraisals the evidence of safety, tolerability, potential,and superior efficacy of spesolimab, a novel IL-36 monoclonal antibody developed by Boehringer Ingelheim. It is recently approved for the treatment of GPP fares in adults in the US, the European Union, and Japan. Spesolimab is a first-in-class medication that changed a paradigm shift in the management of GPP based on evidence-based targeted biologic therapy and clinical success for this distinctive type of psoriasis disease.